2006
DOI: 10.1002/eji.200535068
|View full text |Cite
|
Sign up to set email alerts
|

Role of DC‐SIGN in the activation of dendritic cells by HPV‐16 L1 virus‐like particle vaccine

Abstract: Dendritic cell-specific intercellular adhesion molecule-grabbing non-integrin (DC-SIGN), a specific C-type lectin expressed on DC, binds and transmits different pathogens to susceptible cells. In the present study, we examined the role of DC-SIGN in the capture of human papillomavirus (HPV) pseudovirions and activation of DC. We demonstrate that HPV virus-like particles (VLP) bind to DC-SIGN expressed on transfected Raji cells and that antibodies against DC-SIGN block this interaction. DC take up VLP, which ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 38 publications
3
20
2
Order By: Relevance
“…The pattern of cytokine expression observed in this study is in agreement with results demonstrating the ability L1 VLP to induce potent B cell responses and dendritic cell activation (2,6,8,16,17,20,27). Alternatively, cytokine responses to L1 VLP observed prior to vaccination and in some of the placebo recipients during the study could be due to natural HPV infection that resulted in priming of the PBMCs to the L1 HPV antigens.…”
Section: Discussionsupporting
confidence: 89%
“…The pattern of cytokine expression observed in this study is in agreement with results demonstrating the ability L1 VLP to induce potent B cell responses and dendritic cell activation (2,6,8,16,17,20,27). Alternatively, cytokine responses to L1 VLP observed prior to vaccination and in some of the placebo recipients during the study could be due to natural HPV infection that resulted in priming of the PBMCs to the L1 HPV antigens.…”
Section: Discussionsupporting
confidence: 89%
“…TLR signaling links the innate and adaptive arms of immune response against invading pathogens 50,51 and induces anti-HIV-1 cytokines such as IFN-␣, IL-10, IFN-␥, and MCP-2. 27,28 In the present study, we demonstrated that VLPs can bind to monocytes/ macrophages and induced a novel anti-HIV-1 cytokine, IL-27. To X4-infected CD4 ϩ T cells were cultured for 7 days in the absence or presence of 100 ng/mL recombinant IL-27.…”
Section: Discussionsupporting
confidence: 54%
“…26 Recent studies demonstrate that human papillopma virus-like particles (HPV-VLPs) bind to dendritic cells and are able to induce a range of responses in immune cells, notably the expression of anti-HIV-1 cytokines such as interferon-␣ (IFN-␣), interleukin-10 (IL-10), interferon-␥ (IFN-␥), and monocyte chemotactic protein 2 (MCP-2). 27,28 The HPV-VLP vaccine has been demonstrated to be protective against HPV infection. 29-31 HPV-type 16 (HPV16) represents the primary causative agent of cervical cancer.…”
mentioning
confidence: 99%
“…The apparent discordance of these results could be due to a different optimal timing for the sample collection and needs to be evaluated by more extensive observations. Nevertheless, the production of IFN-␥ by DCs induced with enveloped or nonenveloped VLP produced in different expression systems (prokaryotic, yeast, and baculovirus) is still a debated issue (18,28,30,49,53,54). In particular, Yang et al (53), reported that the CD8␣ ϩ…”
Section: Discussionmentioning
confidence: 99%